Matilda - Dahl, Roald (UK Puffin books Penguin random house, 2016)
Matilda is a sweet, exceptional young girl, but her parents think she's just a nuisance. She expects school to be different but there she has to face Miss Trunchbull, a kid-hating terror of a headmistress. When Matilda is attacked by the Trunchbull she suddenly discovers she has a remarkable power with which to fight back. It'll take a superhuman genius to give Miss Trunchbull what she deserves and Matilda may be just the one to do it!